Weaving, warping, knotting situated feminist genealogies. Addressing challenges of space and time (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
This paper seeks to address the issues implicated in the construction of feminist genealogies. The perspective adopted incorporates several tensions and dilemmas that pervade the feminist field: those arising from class inequalities, from the effects of racialization, and from geographical locations. It also deals with new transformations as the result of the increased participation of younger generations, which have created an age gap. Due to its recent exponential growth and increased public visibility, the feminism is facing complex challenges. On the one hand, we must bring together past and present, recalling the ways our feminist ancestors envisioned the warps and wefts and knots of the movement. We must carry out this work of weaving from Safina Newbery to Silvia Rivera Cusicanqui and Julieta Kirkwood. On the other hand, we must confront the effects of dispersions of age, political traditions, location, class, embodiment, identities, in a moment driven both by the internationalist spirit of the movement as well as its situated character, its local grounds. Methodologically, the work is based on the revision of theoretical debates as well as on documentary searches for the connections between past and present and for the links among the different spaces where feminists are intervening.
Keywords: Feminist Genealogies; Political Experience; Past and Present